Pollen morphology and availability of pollen and stigma in Syzygium (Myrtaceae) - Nacata, Guilherme; Belonsi, Talita Kely; Gasparino, Eduardo Custodio [UNESP]; Andrade, Renata Aparecida de [UNESP] (Soc Brasileira Fruticultura, 2019)
The present study aimed to describe the pollen morphology in three species of Syzygium, to test pollen availability and stigma receptivity. The pollen was analyzed by light and scanning microscopy to show the detailed ornamentation of the pollen grains. Pollen availability was measured according to two protocols. Stigmatic receptivity was tested at different stages of flower development. There are differences among the pollen morphology for the species studied; when the polar and equatorial diameters are measured in the equatorial view of the pollen grains, it is observed that S. jambos is the largest species concerning the two values of the diameters, S. malaccense is the smallest species and S. aqueum, the largest species in relation to the polar diameter in the equatorial view. For the equatorial diameter in equatorial view, S. aqueum showed the smallest diameters and S. malaccense, the major diameters, but the two species overlap in the values of the measured diameters. There are variations in the number of apertures in the pollen grains. Alexander's stain is more sensitive to estimate pollen availability and the species S. aqueum and S. jambos have the same schedules of pollen availability and stigma receptivity.
Keywords: Exotic fruit tree; Palynology; Pollen grains; Stigma; Syzygium